STABILIZING SURGICAL INTERVENTIONS IN THE TREATMENT OF DESTRUCTIVE PATHOLOGICAL HIP DISLOCATION AFTER HEMATOGENOUS OSTEOMYELITIS. - Alpisbaev Kh.Sh; Juraev A.M; Tapilov E.A (Scholar Express Journals, 2023)
The purpose of the study is to analysis of the outcomes of surgical treatment of children with pathological hip dislocation.
Keywords: osteomyelitis; hip; septic arthritis